Spontaneous NETosis in diabetes: A role of hyperglycemia mediated ROS and autophagy - Farhan, Anam; Hassan, Ghulam; Ali, Sheikha Hina Liaqat; Yousaf, Zainab; Shafique, Kandeel; Faisal, Amir; Younis, Bilal bin; Mirza, Shaper (Frontiers in Medicine, 2023)
Abstract Type 2-diabetes, particularly poorly controlled diabetes, is a risk factor for several infections such as lower respiratory tract and skin infections. Hyperglycemia, a characteristic downstream effect of poorly controlled diabetes, has been shown to impair the function of immune cells, in particular neutrophils. Several studies have demonstrated that hyperglycemia-mediated priming of NADPH oxidase results in subsequent elevated levels of reactive oxygen species (ROS). In healthy neutrophils, ROS plays an important role in pathogen killing by phagocytosis and by induction of Neutrophil Extracellular Traps (NETs). Given the key role of ROS in autophagy, phagocytosis and NETosis, the relationship between these pathways and the role of diabetes in the modulation of these pathways has not been explored previously. Therefore, our study aimed to understand the relationship between autophagy, phagocytosis and NETosis in diabetes. We hypothesized that hyperglycemia-associated oxidative stress alters the balance between phagocytosis and NETosis by modulating autophagy. Using whole blood samples from individuals with and without type 2-diabetes (in the presence and absence of hyperglycemia), we demonstrated that (i) hyperglycemia results in elevated levels of ROS in neutrophils from those with diabetes, (ii) elevated levels of ROS increase LCIII (a marker for autophagy) and downstream NETosis. (iii) Diabetes was also found to be associated with low levels of phagocytosis and phagocytic killing of S. pneumoniae. (iv) Blocking either NADPH oxidase or cellular pathways upstream of autophagy led to a significant reduction in NETosis. This study is the first to demonstrate the role of ROS in altering NETosis and phagocytosis by modulating autophagy in type 2-diabetes.